Pesticide genotoxic effect of fipronil in alevins "Gamitana" Colossoma macropomum under laboratory conditions - López, Alberto (2011)
This study evaluates the genotoxic injury in the species Colossoma macropomum (“Gamitana") when exposed to the pesticide Fipronil, for which we used the micronucleus test (MN). We workwed with juveniles in the third stage, placed in glass tanks, which were exposed to 3 different concentrations of fipronil (C1: 0.075 mg /L, C2: 0.15 mg /L and C3: 0.30 mg /L), evaluated at 24 and 48 h. Peripheral blood was used which made the spread. The counting of micronuclei and abnormalities was made on the basis of 1000 cells. The average rate of micronuclei indicates that 0.075 mg / L the average frequency is twice the control. With regard to abnormalities of the core, was found more frequently at 48 h of exposure.